Thirlwall's law with an emphasis on the ratio of export/import income elasticities in Latin American economies during the Twentieth Century - Guerrero de Lizardi, Carlos (Estudios Económicos de El Colegio de México, 2006)
Using stochastic specifications that emphasize the role of the ratio of export/import income elasticities, this paper applies the balance-of-payments constraint model to nineteen Latin American countries from 1900 to 2000. The paper begins with a brief presentation of Thirlwall’s well known model. Immediately following this, we verify the existence of a long run relationship between developing economies on one hand, and the US economy on the other. To explore the short term evolution of the quantitative link between economies, a time varying model is estimated by means of an algorithm known as Kalman Filter. Mainly, the results show a diminishing the ratio of export/import income elasticities over the years, which represents an unexpected and serious feature of the new economic strategy that has already been implanted in the region.